Little David and his best friend - Bowman, Crystal; Endersby, Frank (Grand Rapids, Mich. : Zonderkidz, 2010)
"[T]he life of a blessed mouse whose life parallels that of David the shepherd and king. When David lives at the king's house, he becomes best friends with Prince Jonathan. But the king isn't happy with little David. What should the friends do?"--Publisher's website.
Accelerated Reader
Keywords: Mice -- Juvenile fiction; Friendship -- Juvenile fiction; Jealousy -- Juvenile fiction; Christian life -- Juvenile fiction